Socio-economic Patterns of Obesity Among Aboriginal and Non-Aboriginal Canadians - Ng, Carmina (Can J Public Health, 2011)
OBJECTIVES: Large disparities exist between Aboriginal and non-Aboriginal Canadians in both obesity and socio-economic status (SES). The purpose of this paper was to assess associations between obesity and three indicators of SES–employment, education and income–in conjunction with demographic and lifestyle factors. METHODS: Using the nationally-representative Canadian Community Health Survey (CCHS) cycle 2.2 (2004), among 334 off-reserve Aboriginal and 6,259 non-Aboriginal Canadians aged 25–64 years in the 10 provinces, obesity status was determined by body mass index derived from measured height and weight. Logistic regression was used to assess the relationships between socio-demographic variables and obesity status. RESULTS: Controlling for other socio-economic and lifestyle factors, odds for obesity were lower by 80% among Aboriginal men and 64% among Aboriginal women who were employed during the 12 months prior to the survey compared to Aboriginal men and women who were not employed. Employment was not significantly associated with obesity among non-Aboriginal adults. Probability for obesity increased as household income increased among Aboriginal men, but a negative association between income and obesity was observed among Aboriginal women. These associations persisted after adjustment for physical activity level, fruit and vegetable consumption, smoking, and marital status in the models. CONCLUSION: Unemployment among obese Aboriginal Canadians warrants attention. The knowledge that both high and low SES Aboriginal Canadians, of varying socio-demographic characteristics and lifestyle, experience high rates of obesity can lead to new hypotheses of how obesity develops in this population and influence how interventions are planned.